Examination of secondary school students’ digital gaming motivations and gaming behaviors at different times - Yılmaz, Beyza (Journal of Dependence, 2022)
Objective: This study was carried out to compare the gaming behaviors of secondary school students during the academic year and summer vacation. Method: The research was carried out with the screening model, which is one of the quantitative research methods. Relational design, one of the scanning models, was used to understand the gaming behaviors at different times. The measurement tool of the research consists of three parts: Personal Information Questionnaire, Digital Game Motivation Scale and Online Game Addiction Scale. At a randomly selected high school in Yenimahalle district of Ankara province, the answers of 300 students from 9th, 10th and 11th grades, reached by using the stratified sampling method, at the end of the spring semester and summer vacation of the 2018-2019 academic year, to the questionnaire were analyzed.Results: Students who play games during the academic year are significantly more dependent on online games and have a higher level of motivation to play than students who play during the summer vacation. Students who play games for longer and more frequently both during the academic year and during the summer vacation are more motivated and prone to game addicton to play than those who play for shorter periods, and those who play less frequently.Conclusion: It is expected that the social work discipline, which works to increase the well-being of children and young people, will shed light on digital game playing behaviors with both theoretical and practical studies with its holistic perspective.
Keywords: Digital games; problematic gaming behavior; adolescent